PENGARUH BERBAGAI JENIS DAN DOSIS PUPUK ORGANIK TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN HOTONG (Setaria italica [L.] Beauv) - Masita Masita; J F Rehena; John Riry; Ali Awan (Program Studi Pendidikan Biologi FKIP Unpatti, 2015)
Background: One type of organic fertilizer is manure that contains nutrients that can support the growth of microorganisms in soil fertility and soil. On the island of Buru, the people there know and cultivate community hotong normally used as a traditional food. Methods: This study was conducted in the District Three Village house Baguala, which lasted for four months ie from March to June 2015. The study was conducted in the form of two factor experiment in a randomized complete block design (RAK). The first factor (I) is a type of organic fertilizer (F), which consists of 4 levels of treatment and the second factor (II) is a dose of organic fertilizer (M) comprising 5 stage treatment. Observations were made on indicators of growth in terms of height and number of leaves and production indicators include the number of tillers (JA), the number of panicle (JM), panicle length (PM), planting seed weight (BBP), and the dry weight of stover (BKB). Results: The existence of the effect of the type of organic fertilizer on the growth and poduksi plant hotong seen in the treatment of type of fertilizer week 8 is on F3 and F4 showed high growth of crops, leaf number ever, the number of panicle most, the number of tillers most, panicle length of the longest and most planting seed weight and dry weight of stover. The influence dose of organic fertilizer on the growth and yield of hotong look at treatment week 8, namely the treatment of M2, M3 and M4 showed high growth of crops and the number of leaves, the highest and the treatment number of panicles and tillers most, panicle length of the longest as well as the weight of seed planting and a dry weight of stover. Recommendations effective fertilizer in crop cultivation hotong is to use the type of chicken manure and cow with doses of 900 and 1200 g / polybag. Conclusion: The interaction between treatment types of fertilizers and fertilizers at the variable growth in terms of height (TT) and number of leaves (JD) as well as for variable production panicle length (PM), the weight of the seed crop (BBP) and the dry weight of stover (BKB) showed their influence the type and dose of fertilizer on each variable hotong growth and crop production, reflected in the growth and crop production hotong diverse in every treatment.